POTENSI DAN PERMUDAAN ALAM ROTAN DI KAWASAN HUTAN PRODUKSI TERBATAS (HPT) DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Abdul Hapid; Adam Malik; Hamka Hamka; Yusuf Abd Malik (Universitas Tadulako, 2018)
Non timber forest products are potential assets to generate foreign exchange. One type of plants that has a trade prospect is rattan. The method used belt transects. The size of the plots is 10 m x 100 m along 1000 m. The result showed that there were three types of rattan, namely Batang Rattan (Calamus zollingeri Becc), Ronti Rattan (Calamus axillaris Becc) and Tohiti Rattan (Calamus inops Becc, ex. Heyne). The density was based on the length of the rattan stems: the length <3 m (133 stems/ha), between 3-5 m (58 stems/ha) and> 5 m (146 stems/ha). The highest potential of rattan at all regeneration levels is dominated by Batang rattan (Calamus zollingeri Becc) of seedling level 93.13%, and 122 stems/ha, 87.93% and 51 stems/ha and adult 68.49% and 100 stems/ha. The type of rattan at all levels of natural regeneration was dominated by Batang rattan (Calamus zollingeri Becc) with Import Value Index (INP) of 184.04%, weaning rate of 178.84%, and adult rate of 151.82%. In the type of Ronti Rattan (Calamus axillaris Becc), the seedling level had an Important Value Index (INP) of 15.96%, weaning rate of 21.16% and an adult rate of 39.16%. While the rattan species that had the lowest Importance Index Score (INP) was the lowest in all natural regeneration classes. That was Ronti Rattan (Calamus inops Becc ex Heyne) with Important Value Index (INP) of seedling and weaning rates absent and at adult level with Important Value Index (INP) of 9.02%.